The Aesthetic of Islamic Arts | جمالية الفــــــــن الإسلامي - Mahmoudi Dahbia (Al-Zahra : Journal for Islamic and Arabic Studies, 2020)
The study of Islamic art is an analytical study of its most important features, as it is linked to the Islamic faith. Many studies were conducted around it, which attempted to question its originality and uniqueness from the rest of the arts that were contemporary to it or preceded it, and tried every time to refer its creativity and aesthetics to other arts. However the study of this unique art is a philosophical and intellectual study. At the end of the research, we reached the conclusion that Islamic art is one of the broadest arts, and that the intellectual approach of the Islamic faith had its clear imprint on its forms and contents on various arts. To sum up, the aesthetic of Islamic art was crystallized by the Islamic faith, despite the factors of influence and being influenced.